Analisis Subsektor dan Komoditas Unggulan Pertanian Kabupaten Natuna, Kepulauan Riau, Indonesia - Safitri, Junita Sholekhatun; Surendra, Rahmat Agus (Seminar Nasional Official Statistics, 2025)
The Government of Indonesia promotes regional development by leveraging each region’s unique characteristics and potential, emphasizing the sustainable use of key resources while preserving the environment. Natuna Regency, located in a remote area of Indonesia, faces higher essential goods prices compared to other regions. Therefore, analyzing the leading agricultural subsectors and commodities in this area is crucial. This study aims to (1) identify which agricultural subsectors and commodities are leading (basis) versus non-leading, and (2) map their growth patterns. Data include time-series GRDP for Riau Arcipelago Province and Natuna Regency (2020–2024) and fisheries production (2020–2023). Location Quotient and Klassen Typology are employed. Findings reveal that the food crops and fisheries subsectors are classified as basis (LQ > 1), with leading fisheries commodities like snapper, grouper, and frigate mackerel. The Klassen Typology also places fisheries commodities such as snapper and grouper in the leading category.